Improving The Performance of Informal MSMES Determinate by Digital Financial Inclusion and Digital Financial Literacy - Sekar Budi Pratiwi; Siti Kurnia Rahayu (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to examine and analyses the magnitude of the contribution of increasing digital financial inclusion and increasing digital financial literacy to efforts to increase the employment of Informal MSMEs. The data used is primary data with a closed questionnaire instrument using online media. The study method used is quantitative method. The population of this study is MSMEs in the Bandung City area, where the sample used was 129 Informal MSME actors using a simple random sampling technique because respondents were homogeneous. The data were analysed descriptively and hypothesis testing using analysis path (SPSS version 23.0). Has a result of the study concluded that digital financial literacy has an influence on digital financial inclusion, and digital financial dilution has an influence on the performance of Informal MSMEs, and digital financial iterations have an influence on the performance of Informal MSMEs through digital financial inclusion.